Demand as an important contribution to business performance model of Malay small family food processing industry in Peninsular Malaysia - Jamaluddin, Askiah; Paim, Laily; Abdul Rahim @ Abdul Wahab, Husniyah; Redzuan, Ma'rof (Penerbit MARDI, 2018)
The Malay small family business (MSFB) has a great potential in food processing industry. This is because of the demand on food processing products from domestic consumers. The demand is increasing especially during the festival seasons. High demand from consumer explains about business performance. However, there are several elements that can be explained as business performance. Generally, the financial is a measurement to explain the business performance. Therefore, the purpose of this paper is to highlight the main domain that contributes to business performance model of Malay Small Family Food Processing Industry. This paper employed the Household Production Theory as a research based. This theory is closely related to explain the important of small family business for family wellbeing. Business performance can be reached without reduce the wellbeing of the family. The results of a field survey reveal responses from 70 business owners from four states in Peninsular Malaysia which are Selangor, Perak, Terengganu and Johor. The data was collected within three months. The data was analysed by descriptive analysis and exploratory factor analysis (EFA). Based on EFA, demand is an important contribution to business performance for MSFB. There are four domains that complement to business performance model. The result benefited to the researchers, extension officers and policy makers on overcome the issue of demand.